Expression of caspase-3 and the cytokine level in experimental reperfusion syndrome upon treatment with peroxiredoxin 6 - Kubyshkin, A. V.; Novosyolov, S. V.; Fomochkina, I. I.; Kharchenko, V. Z.; Pisarev, A. A.; Gordeeva, A. E.; Beketov, A. A.; Kochkina, A. V.; Fedosov, M. I.; Anisimova, L. V.; Goncharov, R. G. (Biophysics (Oxford), 2017)
Ischemia-reperfusion injury is a significant problem; there is a need for interpretation of its pathogenetic mechanism and a search for potential methods of correction. The aim of this study was to investigate the cytokine content and the proapoptotic protein expression, including caspase-3, in experimental ischemia–reperfusion injury, and to assess the effectiveness of peroxiredoxin 6 treatment. Studies were conducted on 56 white male Wistar line rats weighing 180–200 g, in which ischemia–reperfusion injury was simulated by cross clamping both hind limbs. Proinflammatory cytokines in blood serum, the expression of caspase-3 in the cells of blood vessels, lungs, and kidneys were analyzed after ischemia–reperfusion injury and upon the peroxiredoxin 6 preventive treatment. It was found that the progression of ischemia–reperfusion injury is followed by proinflammatory cytokine activation in the rat blood: the maximum values of interleukin 1β, which were almost 10 times higher than the control, have been observed by 12 h of reperfusion. Ischemia–reperfusion injury was accompanied by an caspase-3 increase in the cells of rat limb vessels and the lungs after 6 h of reperfusion. Peroxiredoxin 6 treatment neutralizes oxidative stress primarily in the limb blood vessels, reducing the degree of vessel tissue destruction in the hind limbs that should be considered as a target for therapy of ischemia–reperfusion injury.